Triptolide Induces Glioma Cell Autophagy and Apoptosis via Upregulating the ROS/JNK and Downregulating the Akt/mTOR Signaling Pathways - Liu, Xihong; Zhao, Peiyuan; Wang, Xiujuan; Wang, Lei; Zhu, Yingjun; Gao, Wei (Frontiers in Oncology, 2019)
Apoptosis and autophagy are the two prominent forms of developmental cell death, and researches have shown that crosstalk exists between these two processes. A prior study demonstrated that triptolide inhibited the proliferation of malignant glioma cells. However, whether apoptosis and autophagy participate in the inhibitory effect of triptolide in glioma cells has not been clarified. In the present study, we demonstrated that triptolide potently inhibited the growth of glioma cells by inducing cell cycle arrest at the G2/M phase. Additionally, the treatment with triptolide induced apoptosis and autophagy in various glioma cell lines. Triptolide-induced autophagy may have tumor-supporting effects. Autophagy and apoptosis could cross-inhibit each other in glioma cells treated with triptolide. Moreover, we found that triptolide induced ROS production and JNK activation and inhibited the activity of Akt and mTOR. Finally, we demonstrated that triptolide suppressed tumor growth in an orthotopic xenograft glioma model. Collectively, these data indicated that triptolide induced G2/M phase arrest, apoptosis, and autophagy via activating the ROS/JNK and blocking the Akt/mTOR signaling pathways in glioma cells. Triptolide may be a potential anti-tumor drug targeting gliomas.